PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 019 LENGGADAI HULU KECAMATAN RIMBA MELINTANG - Masna Masna; Zetra Hainul Putra; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Internal issue background in this research is that students do not really understand science lesson. This problem can be seen from the low of students’ science result with the average 67, as well as still lower the attainment of minimum completeness criteria (KKM) namely, from 20 students only 7 students or 35% reach the KKM. KKM specified by the school is 73. As for becoming target in this research is to improve the students’ learning result in study science of grade V SD Negeri 019 Lenggadai Hulu through applying cooperative learning model. For the activity of learn at first meeting equal to 58,33% raise at second meeting become 66,67% ( 8,34%), from the second meeting to first meeting of cycle II become 83,33% (16,66%), and from first meeting to second meeting become 87,5% ( 4,17%). For the students’ activity at first meeting equal to 54,17% increase to second meeting become 62,5% (8,33%), from second meeting to first meeting of cycle II become 75% (12,5%), and from first meeting to second meeting become 83,33% ( 8,33%).Students’ learning result also increase from 67 to 78 in the first cycle (raise 16,42%) and increase about 33,81% in the second meeting becoming 89,75. It is also happened by the make-up of classical complete activity from 35% at restating of cycle I reach as much 20% so that percentage become 55% and at restating of cycle II raise as much 40% so that percentage become 95%. Finally, it can be concluded that applying cooperative learning model can improve science learning result of grade V SD Negeri 019 Lenggadai Hulu.Keywords: Cooperative Learning Model, Science Learning Result, Classroom Action Research